Size Distributions for All Cities: Lognormal and q-exponential functions - Rafael González-Val; Arturo Ramos-Gutiérrez; Fernando Sanz-Gracia (European Regional Science Association (ERSA), 2011)
This paper analyses in detail the features offered by a function which is practically new to Urban Economics, the q-exponential, in describing city size distributions. We highlight two contributions. First, we propose a new and simple procedure for estimating their parameters. Second, and more importantly, we explain the characteristics associated with two traditional graphic methods (Zipf plots and cumulative density functions) for discriminating between functions. We apply them to the lognormal and q-exponential, justifying them as the best functions for explaining the entire distribution, and that the relationship between them is of complementarity. The empirical evidence relies on the analysis of urban data of three countries (USA, Spain and Italy) over all of the 20th century.
Keywords: 330